Ag/AgO nanoparticles: Green synthesis and investigation of their bacterial inhibition effects. (2021) - Abdalameer, Nisreen Kh.; Khalaph, Kawther A.; Ali, Ehab M.
Abstract: In this study, Ag/AgO NPs were synthesized by Crocus sativus L Extract in a single step biosynthesis. It acts as an agent to reduce and cap. Nanoparticles were characterized by UV–Visible spectra, X-ray diffraction (XRD). The Plasmon resonance surface (Ag / AgO NPs) of the as-prepared surface showed a Plasmon resonance at 410 nm. The XRD pattern showed Ag and AgO peaks. The mean crystalline size of Ag is 28.25 nm and 26.21 nm for AgO. Electron microscope field emission scanning (FESEM) was used to study the morphology of the Ag/AgO NPs. The biological test results demonstrated the effect of silver nanoparticles on different types of a bacterium: gram-positive, gram-negative, as different inhibitors for each type were registered and the impact of silver material on bacteria inhibition was shown.